Metastatic colorectal adenocarcinoma in a 76-year old male: a pitfall in the diagnosis for unclassified renal cell carcinoma - Dafne C. Andrade; Sheila F. Faraj; Leopoldo Alves Ribeiro Filho; Romulo L. Mattedi (BMC, 2019)
Abstract Background The kidney is the most common site of metastatic disease to the urinary tract. However, tumor characteristics are commonly deceptive, and the diagnosis of metastatic disease to the kidney may be challenging. Case presentation A 76- year old male was submitted to a total left nephrectomy with splenectomy due to pyonephrosis. At gross examination, the kidney presented a distorted anatomy, with firm parenchyma and an extensively necrotic lesion occupying the renal pyelo-calix and ureter. The spleen had a white pericapsular lesion measuring 1.2 cm. Histologic sections demonstrated a high grade solid carcinoma with rare areas of tubular differentiation. The tumor was highly infiltrative, with invasion of the renal sinus, perirenal fat and spleen. Considering the tumor location, high grade and infiltrative growth pattern, the diagnostic hypothesis of collecting duct carcinoma and urothelial carcinoma were drawn and investigated. Furthermore, a suspicion of metastatic disease was raised after a thorough investigation of the patient's chart, which revealed a previous history of colorectal carcinoma 4 years earlier. Immunohistochemical studies demonstrated expression of CK20 and CDX-2 and negativity for CK7, CK5, PAX-8, Vimentin, CD117, GATA3 and p63; therefore, the patient was diagnosed with a poorly differentiated metastatic colorectal adenocarcinoma. Conclusion A high degree of suspicion is necessary for the diagnosis of metastatic disease to the kidney, which should ruled out before the final diagnosis of an unclassified renal cell carcinoma. A careful examination of the patient's history and adequate communication with the attending physician is recommended for the correct diagnosis of these cases.